Digital Technologies and Applications Proceedings of ICDTA’22, Fez, Morocco, Volume 2 - Motahhir, Saad; Bossoufi, Badre (Lecture Notes in Networks and Systems, 2022)
XX, 846 p. 491 illus., 405 illus. in color.